Inkjet printing heterostructures for optoelectronic device applications - Austin, Jonathan (2024)
Devices that combine the tuneable optical properties of 0-dimensional (0D) materials, such as perovskite nanocrystals (NCs), with the unique electrical properties of 2-dimensional (2D) layers, such as graphene, are promising candidates for the next generation of optoelectronics. However, these high-performance devices typically require bespoke fabrication techniques and are yet to reach commercial viability. Inkjet printing can offer a promising route for scalable manufacturing of devices on various substrates from Si/SiO2 to flexible polymers. However, many functional nanomaterials have not yet been formulated or optimised for deposition via inkjet printing and the fully printed heterostructures needed for many optoelectronic devices have proven challenging to fabricate.